Changes in adiposity levels in schoolchildren according to nutritional status: analysis over a 30-year period - Gerson Luis de Moraes Ferrari; Mario Maia Bracco; Mauro Fisberg; Victor Keihan Rodrigues Matsudo (Universidade Federal de Santa Catarina, 2013)
The aim of this study was to analyze changes in adiposity levels over a 30-year period in schoolchildren according to nutritional status. This study is part of Projeto Misto Longitudinal de Crescimento, Desenvolvimento e Aptidão Física de Ilhabela. 1.144 schoolchildren of both sexes, aged between 10 and 11 years, met the following inclusion criteria: (a) have at least one complete evaluation in one of the analyzed periods; (b) be in the prepubertal stage of sexual maturation;and (c) be apparently healthy. Analyzed periods were 1978/1980 (Baseline),1988/1990 (10 years), 1998/2000 (20 years), 2008/2010 (30 years). Analyzed variables were: body mass (kg), height (cm) and adiposity levels (mm). Children were classified into three categories: eutrophic, overweight and obese, according to nutritional status, using World Health Organization (WHO) body mass index (BMI) curves for age and sex. For a comparison between periods, Two-Factor Analysis of Variance and Bonferroni's test were used. In both sexes, the most significant increase in adiposity levels occurred among the eutrophic group, followed by the overweight group and obese group. Results showed an increase in adiposity levels over a 30-year period, even with nutritional status control. It shows that individuals with a similar BMI may vary in proportion and distribution of subcutaneous adipose tissue.